Applied Behavior Analysis for Motor Imitation Development in Elementary School Children with Autism Spectrum Disorder - Munir, Muniroh; Mumpuniarti, Mumpuniarti (Journal of Innovation and Research in Primary Education, 2025)
Motor imitation deficits represent a significant challenge for children with autism spectrum disorder (ASD), affecting social communication, observational learning, and adaptive skill development. Applied Behavior Analysis (ABA) has demonstrated effectiveness for various autism interventions, yet limited research has specifically examined its application to motor imitation skills in elementary school settings. This study investigated the effectiveness of ABA intervention strategies in improving motor imitation abilities among children with autism in an educational context. A single-subject research design with A-B-A phases was employed with a six-year-old elementary school student diagnosed with mild autism. The intervention utilized Discrete Trial Training and Natural Environment Training techniques over 15 sessions across three weeks. Motor imitation performance was assessed using structured observation of five behavioral indicators, scored on a four-point scale. Data collection included direct observation, stakeholder interviews, and documentation analysis to ensure comprehensive evaluation and triangulation. The intervention demonstrated substantial effectiveness, with mean motor imitation scores increasing from 1.0 during baseline to 2.8 during intervention, representing a 180% improvement. Following intervention withdrawal, performance maintained at 2.4, indicating 140% sustained improvement above baseline levels. Qualitative data from parent and teacher interviews corroborated improvements, reporting enhanced spontaneous imitation behaviors and improved responsiveness to instructions in natural environments. Academic performance in motor-related subjects showed concurrent improvements. The findings validate ABA effectiveness for addressing motor imitation deficits in autism within educational settings. Results align with behavioral learning principles and extend the evidence base for systematic motor interventions. The sustained improvements and successful generalization across environments support the integration of ABA strategies in elementary school programming for children with autism.